Efficacy and Safety of Daprodustat for Anemia Therapy in Chronic Kidney Disease Patients: A Systematic Review and Meta-Analysis - Zheng, Qiyan; Wang, Yahui; Yang, Huisheng; Sun, Luying; Fu, Xinwen; Wei, Ruojun; Liu, Yu Ning; Liu, Wei Jing (Frontiers in Pharmacology, 2021)
Objective: Daprodustat is a novel oral agent in treating anemia of chronic kidney disease (CKD), and several clinical trials have been conducted to compare daprodustat with recombinant human erythropoietin (rhEPO) or placebo. Our systematic review aimed to investigate the efficacy and safety of daprodustat for anemia treatment in both dialysis-dependent (DD) and non-dialysisdependent (NDD) patients.Methods: Six databases were searched for randomized controlled trials (RCTs) reporting daprodustat versus rhEPO or placebo for anemia patients in CKD. The outcome indicators were focused on hemoglobin (Hb), ferritin, transferrin saturation (TSAT), total iron-binding capacity (TIBC), vascular endothelial growth factor (VEGF), and serious adverse events (SAEs).Results: Eight eligible studies with 1516 participants were included. For both NDD and DD patients, changes in Hb levels from baseline were significantly higher in daprodustat group than that in the placebo (mean difference (MD)=1.73, [95% confidence interval (CI), 0.34 to 3.12], P=0.01; MD=1.88, [95% CI, 0.68 to 3.09], P=0.002; respectively), and there was no significant difference between daprodustat and rhEPO group (MD=0.05, [95% CI, -0.49 to 0.59], P=0.86; MD=0.12, [95% CI, -0.28 to 0.52], P=0.55; respectively). The indexes of iron metabolism were improved significantly in the daprodustat group compared to placebo-or rhEPO-treated patients, while there